2020
DOI: 10.1186/s12886-020-01541-7
|View full text |Cite
|
Sign up to set email alerts
|

Macular hole edge morphology predicts restoration of postoperative retinal microstructure and functional outcome

Abstract: Background: To investigate the ability of intraoperative optical coherence tomography (iOCT) during macular hole (MH) surgery to image different hole edge configurations and predict the restoration of retinal microstructure and visual outcomes. Methods: This retrospective case series study included 53 MH patients. One eye each was assessed with iOCT during vitrectomy after internal limiting membrane (ILM) peeling. The MHs were categorized into three groups according to the morphology of the hole edge. The Hole… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
4
1
Order By: Relevance
“…This might be explained by the contractile capability of the leftover pieces, which could hinder the healing process of the outer retina. These conclusions are only partially in accordance with what was subsequently described by Tao et al [ 18 ], leaving the matter unsettled and requiring further research to better understand the correlation between intraoperative tissue configuration and postoperative anatomical and functional outcomes. Further research in this field is also necessary to elucidate the correlation between FTMH healing after the inverted ILM flap technique and the functional outcome, especially considering recent studies suggesting that this technique does not have additional benefits for small–medium-size FTMHs, and may delay recovery of retinal integrity [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This might be explained by the contractile capability of the leftover pieces, which could hinder the healing process of the outer retina. These conclusions are only partially in accordance with what was subsequently described by Tao et al [ 18 ], leaving the matter unsettled and requiring further research to better understand the correlation between intraoperative tissue configuration and postoperative anatomical and functional outcomes. Further research in this field is also necessary to elucidate the correlation between FTMH healing after the inverted ILM flap technique and the functional outcome, especially considering recent studies suggesting that this technique does not have additional benefits for small–medium-size FTMHs, and may delay recovery of retinal integrity [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 73%
“…Tao et al aimed at retrospectively investigating the ability of iOCT to assess different FTMH margin structures and anticipate the recovery of visual function and retinal architecture [ 18 ]. Fifty-three eyes were included and intraoperatively scanned with Optovue iVue OCT System (Optovue, Inc., Fremont, CA, USA).…”
Section: Resultsmentioning
confidence: 99%
“…This was consistent with the results of Kumar ( 21 ). Previous research reported that RF was similar to the inverted ILM flap mechanism ( 17 ); the RFs provided a bridge for the centripetal movement of Muller cells. However, Makoto ( 22 ) observed that postoperative BCVA was worse in patients with iMH and RFs than those without them.…”
Section: Discussionmentioning
confidence: 90%
“…This was contrary to previous findings ( 8 – 10 ). Since Michalewska reported the inverted ILM flap in 2014, researchers have generally believed that it can improve hole closure rates and visual function in patients with refractory MH ( 7 , 17 ), but most previous studies involved few cases and did not assess postoperative ELM reconstruction. Recent studies have reported results similar to those of our study ( 10 , 16 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…6 Intraoperative optical coherence tomography studies have subjected the relation of large FTMH edge/flap configuration at the end of surgery with closure outcomes. 7 Interestingly, cases with adherent foveal flap to the FTMH edge and those with vertical pillars of tissue at the edges of FTMH projecting into the vitreous cavity (“hole-door sign”) had an excellent closure rate in comparison with those with no ILM/tissue remnants at the FTMH edge. 8 This point led us to hypothesize that the sole presence of the peeled ILM with its inner borders being adherent to the edge of the FTMH—regardless of approximation of flap to retinal surface—may be the main factor enhancing the outcome of the procedure.…”
mentioning
confidence: 98%